1976
DOI: 10.1042/bj1590409
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the catalytic subunit of adenosine 3':5'-cyclic monophosphate-dependent protein kinase from bovine liver

Abstract: 1. The catalytic subunit of bovine liver cyclic AMP-dependent protein kinase (EC2.7.1.37) was purified essentially by the method of Reimann & Corbin [(1976) Fed. Proc. Fed. Am. Soc. Exp. Biol. 35, 1384]. 2. Sodium dodecyl sulphate/polyacrylamide-gel electrophoresis, sedimentation-velocity centrifugation and sedimentation-equilibrium centrifugation showed that the catalytic subunit was monodisperse. Polyacrylamide-gel isoelectric-focusing electrophoresis revealed the presence of at least three isoenzyme for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
2

Year Published

1977
1977
1998
1998

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(109 citation statements)
references
References 41 publications
7
100
2
Order By: Relevance
“…On the basis of electrofocussing experiments, several investigators have reported that preparations of the bovine catalytic subunit contain at least three isozymes with identical substrate specificities (9,28,29). However, no primary structure heterogeneity was detected in the present study of the isozyme mixture.…”
Section: Resultscontrasting
confidence: 50%
“…On the basis of electrofocussing experiments, several investigators have reported that preparations of the bovine catalytic subunit contain at least three isozymes with identical substrate specificities (9,28,29). However, no primary structure heterogeneity was detected in the present study of the isozyme mixture.…”
Section: Resultscontrasting
confidence: 50%
“…If the activity of the protein kinase is expressed in terms of its ability to catalyze phosphorylation of histone, 1000-10,000 units/assay was routinely used. It should be emphasized that these protein kinase concentrations are in the physiological range (16). The need to use these levels of protein kinase may explain why previous attempts to phosphorylate rabbit hepatic Fru-P2ase were unsuccessful (22 (1977) in the in vivo phosphorylation of Fru-P2ase (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken gizzard myosin light chains [3,6], myosin light chain kinase [2,7] and CAMPdependent protein kinase [8] were purified as described. Trypsin (treated with tosylphenylchloromethyl ketone) and chymotrypsin were from Boehringer.…”
Section: Methodsmentioning
confidence: 99%